Plastid-cytosol partitioning and integration of metabolic pathways for APS/PAPS biosynthesis in Arabidopsis thaliana - Bohrer, Anne-Sophie; Kopriva, Stanislav; Takahashi, Hideki (Frontiers in Plant Science, 2015)
Plants assimilate sulfate from the environment to synthesize biologically active sulfur-containing compounds required for growth and cellular development. The primary steps of sulfur metabolism involve sequential enzymatic reactions synthesizing adenosine 5′-phosphosulfate (APS) and 3′-phosphoadenosine 5’-phosphosulfate (PAPS). Recent finding suggests that an adenosine nucleotide transport system facilitating the exchange of PAPS and 3′-phosphoadenosine 5′-phosphate across the plastid envelope is essential for establishing an intimate connection between the plastidic and cytosolic sulfate assimilation pathways in plants. Subcellular partitioning and integration of metabolic pathways provide focal points for investigating metabolic flux regulations. This perspective article presents an integrative view of sulfur metabolic flux control mechanisms with an emphasis on subcellular partitioning of APS/PAPS biosynthetic pathways in Arabidopsis thaliana.